Six Different Point Mutations in Seven Danish Families with Symptomatic Protein C Deficiency - Lind, Bent; Schwartz, Marianne; Thorsen, Sixtus (Thrombosis and Haemostasis, 1995)
Six different point mutations of the protein C gene are described in seven Danish families with protein C deficiency associated with an increased risk of venous thromboembolism. All affected family members are heterozygotes for the mutated protein C genotype. One mutation is a G2992→A transition at position +5 in the 5’ splice site of intron D. The other five mutations affect the protein coding region. One is a Cl432→T transition in exon III converting the highly conserved Arg15 to Trp in the Gla-domain. Another mutation is a G3157→C transversion in exon V converting the non-conserved Gly72 to Arg in the epidermal growth factor domain. The remaining three mutations are located in non-conserved amino acid positions in exon IX and affect the serine proteinase domain. The first is a G8559→C transversion converting Gly282 to Arg. The second is a C8571→T transition (present in two families) converting Arg286 to Cys. The third is a C8695→T transition converting Pro327 to Leu. In each family the protein C deficiency cosegregates or probably cosegregates (one family, G8559→C) with the mutation. All affected family members exhibit a reduction of both the antigen and the functional plasma concentration of protein C to approximately 50% of normal indicating that the mutated protein C is not present (type 1 deficiency) or only present in low amounts in plasma. Agarose gel electrophoresis followed by Western blotting shows that the Arg15→Trp substitution is associated with a normal as well as an abnormal migrating plasma protein C band. This provides positive evidence for that both the normal and mutated alleles are expressed (type 2 deficiency). The five other mutations are associated with only one band with the mobility of normal protein C. In one family a novel G1390→A transition converting the normal Ala1 to Thr was demonstrated. This mutation is not linked to the patient specific G8559→C transversion. In conclusion one splice site mutation and five different missense mutations of the protein C gene are described.